Manajemen Program Bimbingan Belajar Bahasa Arab Berbasis Blended Learning Bagi Mahasiswa - Maftukhah, Nuriatul; Mufidah, Nuril (UMSU, 2024)
Bangsal Sinau tutoring institution is one of the basic Arabic language tutoring programs. Learning is carried out offline and online. This research aims to describe the program management process based on management principles. The method in this research is descriptive qualitative case study type. The theory used is the principle of management according to Henry Fayol which consists of the principles of division of tasks, discipline, unity of direction, and initiative. Data collection techniques were observation, interview, and documentation. The main data source is Bangsal Sinau tutoring center. The results show that Bangsal Sinau tutoring center applies the principle of division of labor in the form of grouping teachers according to their language skills. The principle of discipline is interpreted by teachers who are never late for teaching both online and offline, and managers who always remind teachers through WhatsApp groups. The principle of unity of direction is in the form of determining the teaching model, namely group discussions, and using the same teaching materials. The principle of initiative is applied to the innovation of creating a new Instagram account that was released in early 2023, namely @bangsal.sinau, as well as the innovation of the process of making personalized teaching modules that suit student needs. The application of these principles makes this program maintain its quality and continues to exist in demand by students.